A method for in-situ dispersion preparation of modified polyethylene by graphene
Patent Information
- Application Number
- CN202610804748.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-05
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]本发明的目的在于针对现有物理共混工艺石墨烯易团聚、分散差、改性成本高、成品导热/抗静电/阻隔性能提升幅度有限的缺陷,本发明提供一种石墨烯原位分散制备改性聚乙烯的方法
[0015]本发明石墨烯改性聚乙烯颗粒材料,材料应用于高阻隔食品包装薄膜、地热输送管材、汽车内饰改性塑料、5G设备散热外壳原料。
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing modified polyethylene by in-situ dispersion of graphene, and more specifically, to a production method for preparing modified polyethylene with high thermal conductivity, antistatic properties, and high barrier properties by in-situ dispersion polymerization of graphene, belonging to the field of polyethylene modified polymer material preparation technology. Background Technology
[0002] Polyethylene (PE) is the world's largest general-purpose plastic in terms of production capacity and consumption. With its excellent chemical resistance, superior molding and processing characteristics, and low raw material cost, it can be molded through processes such as blow molding, extrusion, and injection molding, and is widely used in oil and gas pipelines, food packaging, automotive parts, and electronic components. However, pure polyethylene's excessively high insulation, poor thermal conductivity, and insufficient gas barrier properties limit its application in high-end fields such as antistatic packaging, thermally conductive geothermal pipes, 5G heat dissipation shells, and high oxygen barrier preservation films.
[0003] Currently, the mainstream preparation method for graphene-modified polyethylene in the industry is melt physical blending, which involves high-temperature mixing and modification of finished polyethylene particles with graphene powder. This process has significant drawbacks: graphene nanosheets have a large specific surface area and strong van der Waals forces between the sheets, making it difficult to break up the agglomerated graphene during melt mixing. This results in uneven dispersion of graphene agglomerates, significantly reducing the modification effect. To achieve the desired performance, the amount of graphene added needs to be greatly increased, leading to a significant increase in raw material costs.
[0004] Most existing chemical modification technologies lack an in-situ solvent dispersion step before polymerization. Graphene is prone to agglomeration during polymerization, resulting in limited improvement in the thermal conductivity, antistatic properties, and barrier properties of the final product. Pre-dispersing graphene at the nanoscale uniformly in an inert polymerization solvent, followed by in-situ ethylene polymerization to anchor the polymer chains to the graphene sheets, inhibits agglomeration at the polymerization source, and is an effective way to address the shortcomings of existing technologies. A literature search revealed no similar technical solutions for preparing modified polyethylene using the in-situ dispersion and Ziegler-Natta catalytic homopolymerization process of this invention. The modified polyethylene exhibits a 3-5 times increase in thermal conductivity, improved wear resistance and tensile properties, and a more than 50% reduction in gas permeability. The modified product can be used in various fields such as corrosion-resistant oil and gas pipelines (extending service life by 30%), lightweight aerospace components, and antibacterial and environmentally friendly packaging, with broad market application prospects. Summary of the Invention
[0005] The purpose of this invention is to address the shortcomings of existing physical blending processes, such as easy agglomeration of graphene, poor dispersion, high modification costs, and limited improvement in the thermal conductivity, antistatic properties, and barrier properties of the finished product. This invention provides a method for preparing modified polyethylene by in-situ dispersion of graphene. Before ethylene polymerization, this invention achieves fine dispersion of graphene in an inert organic solvent. A compound Ziegler-Natta catalyst is used to achieve homogeneous polymerization of ethylene and 1-butene. The graphene sheets are fixed by the polymerized molecular chains, avoiding secondary agglomeration. This allows for the preparation of highly thermally conductive, antistatic, and highly barrier modified polyethylene granules under low graphene addition conditions.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solution: This invention discloses a method for preparing modified polyethylene through in-situ dispersion of graphene, wherein the entire process is carried out under nitrogen inert protection. The method includes the following preparation steps: (1) Preparation of graphene in situ dispersion: Graphene raw material is added to an inert organic solvent and homogenized at high speed for 1 to 3 hours under the conditions of 30 to 50°C and 7000 to 14000 rpm to obtain graphene in situ dispersion; the inert organic solvent is selected from any one of cyclohexane, n-heptane, and xylene; the graphene sheet diameter is 50 to 200 nm, the number of layers is ≤3, and the purity is >99.5%; the amount of graphene added is 0.3 to 2.0 parts by mass based on the mass of the inert organic solvent. (2) Catalytic polymerization reaction: The in-situ dispersion was transferred to a polymerization reactor, and the Ziegler-Natta composite catalyst was added. After the temperature was raised to the polymerization temperature, ethylene, the comonomer 1-butene, and a trace amount of hydrogen were introduced. Homogeneous polymerization was carried out at a constant temperature for 1 hour to obtain a polyethylene-graphene composite dispersion. The Ziegler-Natta catalyst was composed of titanium tetrachloride as the main catalyst, diethylaluminum chloride and MAO as the co-catalyst. The mass concentration of the main catalyst in the dispersion was 0.05-0.15 wt%, the total mass concentration of the co-catalyst was 0.1-0.4 wt%, and the mass ratio of diethylaluminum chloride to MAO was 10:1-20:1. The polymerization temperature was 130-150℃. Based on the total molar amount of ethylene, the amount of 1-butene added was 2-4 mol%. (3) Flash evaporation and solvent removal: The polyethylene-graphene composite dispersion is flash-evaporated at a constant temperature to remove residual inert solvent and unreacted monomers, and graphene-modified polyethylene melt is obtained. (4) Extrusion granulation: The modified polyethylene melt is extruded and granulated by screw extrusion at a temperature of 210-230℃ to obtain graphene modified polyethylene granules.
[0007] Preferably, the inert organic solvent is n-heptane.
[0008] Preferably, the graphene sheet diameter is 100-200 nm, and the amount of graphene added is preferably 0.7-1.2 parts by mass of the inert organic solvent.
[0009] Preferably, the ratio of the co-catalyst diethylaluminum chloride to MAO is 12:1 to 15:1.
[0010] Preferably, the amount of 1-butene added is 3-4 mol% of the ethylene molar amount, and the polymerization temperature is preferably 140-150℃.
[0011] Preferably, the homogenization conditions in step (1) are a temperature of 35-45℃, a rotation speed of 9000-12000rpm, and a homogenization time of 1.5-2.5h.
[0012] Preferably, the extrusion granulation process in step (4) is preferably carried out at a temperature of 215–225°C.
[0013] Preferably, trace amounts of hydrogen are used as molecular weight regulators during the polymerization stage to control the melt flow rate of the finished polyethylene.
[0014] Preferably, the product performance indicators meet the following requirements: melt flow rate > 2.0 g / 10 min under 2.16 kg weight conditions, density < 0.945 g / cm³, oxygen permeability < 20 cm³ / (m²・24h・atm), and surface resistivity < 10. 7 Ω, thermal conductivity >0.51W / (m・K).
[0015] This invention relates to graphene-modified polyethylene granular materials, which can be used in high-barrier food packaging films, geothermal transmission pipes, modified plastics for automotive interiors, and raw materials for heat dissipation shells of 5G equipment.
[0016] Beneficial effects: This invention improves the dispersion effect of graphene flakes and reduces graphene agglomeration by in-situ dispersion of graphene in an inert organic solvent; the homogeneous polymerization of ethylene yields a polyethylene-graphene dispersion, and the viscosity of the dispersion gradually increases, maintaining the dispersion effect of graphene; the graphene-modified polyethylene melt is sheared by a twin-screw extruder, further improving the dispersion level of graphene; the graphene-modified polyethylene prepared by this invention enhances the thermal conductivity, antistatic properties, and oxygen barrier properties of polyethylene, making it suitable for many fields such as packaging and geothermal pipes where high performance is required. Detailed Implementation
[0017] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to specific examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0018] Technical solution / principle:
[0019] This invention discloses a method for preparing modified polyethylene through in-situ dispersion of graphene, using a nitrogen-inert environment throughout the process, comprising four preparation steps: 1. Raw material composition limitations (1) Inert organic solvent: selected from one of cyclohexane, n-heptane, and xylene, with n-heptane being preferred; the solvent has strong chemical inertness, does not participate in the polymerization reaction under polymerization conditions, has excellent wetting and dispersion effect on graphene, and can be recycled after flash evaporation; (2) Graphene: sheet diameter 50-200nm, number of layers ≤3, purity >99.5%; preferably sheet diameter 100-200nm; based on the mass of inert organic solvent, the amount of graphene added is 0.3-2.0 parts by mass, preferably 0.7-1.2 parts by mass; thin-layer high-purity graphene is easier to peel and disperse, and no impurities interfere with the catalytic polymerization reaction; (3) Catalytic system: Ziegler-Natta composite catalyst, the main catalyst is titanium tetrachloride, and the co-catalyst is a mixture of diethylaluminum chloride and MAO; the mass concentration of the main catalyst in the dispersion is 0.05-0.15 wt%, and the total mass concentration of the co-catalyst is 0.1-0.4 wt%; the mass ratio of diethylaluminum chloride to MAO is 10:1-20:1, and the preferred ratio is 12:1-15:1; the composite co-catalyst synergistically optimizes the catalytic activity and ensures stable homopolymerization of ethylene; (4) Comonomer: main monomer ethylene, modified comonomer 1-butene, the amount of 1-butene added is 2-4 mol% of the total molar amount of ethylene, preferably 3-4 mol%; a trace amount of hydrogen is introduced into the polymerization process as a molecular weight regulator; the polymerization reaction temperature is 130-150℃, preferably 140-150℃.
[0020] 2. Specific preparation steps (1) Preparation of graphene in situ dispersion: The whole set of equipment is replaced with nitrogen to remove oxygen in advance and the nitrogen atmosphere is sealed; the selected inert organic solvent is added to the homogenizer, the appropriate amount of graphene is added, the ambient temperature is controlled at 30-50℃, the homogenization speed is 7000-14000rpm, and the high-speed homogenization is stirred for 1-3h; the preferred process parameters are: temperature 35-45℃, speed 9000-12000rpm, and homogenization time 1.5-2.5h; the graphene sheets are peeled off by high-speed shearing to obtain agglomerate-free graphene in situ dispersion.
[0021] (2) Catalytic polymerization reaction: The in-situ dispersion was transferred to the polymerization reactor, and the main catalyst titanium tetrachloride and the compound co-catalyst were added in sequence and stirred and mixed. After the temperature was raised to the polymerization temperature of 130-150℃, ethylene, 1-butene and trace amount of hydrogen were introduced and homogeneous polymerization was carried out at a constant temperature for 1 hour. Ethylene underwent homogeneous polymerization and molecular chain growth. The polyethylene chain segments wrapped around and coated the graphene sheets. As the polymerization proceeded, the viscosity of the system gradually increased, constraining the graphene sheets to agglomerate again, and a polyethylene-graphene composite dispersion was obtained. The molecular weight of polyethylene was adjusted by trace amount of hydrogen, thereby controlling the melt flow rate of the product.
[0022] (3) Flash evaporation and solvent removal: The polyethylene-graphene composite dispersion is sent to a flash evaporation equipment for constant temperature flash evaporation to remove the residual inert solvent and unreacted ethylene and 1-butene monomers in the system. The solvent and monomers are recovered and recycled to obtain graphene-modified polyethylene melt.
[0023] (4) Extrusion granulation: The modified polyethylene melt is fed into a twin-screw extruder, and the extrusion processing temperature is controlled at 210-230℃, preferably 215-225℃; the twin-screw shear further refines and disperses a small amount of residual agglomerated graphene, and the melt is extruded, water-cooled and granulated to obtain graphene modified polyethylene granules.
[0024] 3. Finished Product Performance Parameters The graphene-modified polyethylene particles prepared according to the process of this invention have the following properties: melt flow rate > 2.0 g / 10 min under the test conditions of 2.16 kg weight, density < 0.945 g / cm³, oxygen permeability < 20 cm³ / (m²・24h・atm), and surface resistivity < 10. 7 Ω, thermal conductivity >0.51W / (m・K).
[0025] Example: All performance tests of the product of this invention are conducted in accordance with national standards: density according to GB / T1845.1-2016; melt flow rate according to GB / T3682.1-2018A method; surface resistivity according to GB / T1410; thermal conductivity according to GB / T10801.1-2021; oxygen permeability according to GB / T1038-2000; and the film thickness is uniformly 0.01 mm. Specific embodiments of this invention also include embodiments formed using all left-endpoint values, all right-endpoint values, and all intermediate values of the range parameters. These embodiments should not be construed as limiting the technical solution.
[0026] Comparative example (without graphene):
[0027] The inert solvent used was n-heptane; the main catalyst concentration was 0.05 wt%, the total co-catalyst concentration was 0.1 wt%, and the ratio of diethylaluminum chloride to MAO was 20:1; the polymerization temperature was 130℃, and the addition amount of 1-butene was 2 mol% of the molar amount of ethylene. No graphene was added throughout the process. Test results: melt flow rate 2.3 g / 10 min, density 0.944 g / cm³, surface resistivity 2 × 10⁻⁶. 12 Ω, thermal conductivity 0.35W / (m・K), oxygen permeability 34cm³ / (m²・24h・atm); pure polyethylene has excessive insulation and poor thermal conductivity and barrier properties.
[0028] Example 1:
[0029] Solvent: n-Heptane; Graphene sheet diameter 50nm, addition amount 0.3 parts; Main catalyst 0.05wt%, total concentration of co-catalyst 0.1wt%, diethylaluminum chloride:MAO = 20:1; Polymerization temperature 130℃, 1-butene molar weight of ethylene 2mol%; Finished product specifications: MFR = 2.4g / 10min, density 0.943g / cm³, surface resistivity 7×10⁻⁶ 6 Ω, thermal conductivity 0.52W / (m・K), oxygen permeability 18cm³ / (m²・24h・atm).
[0030] Example 2:
[0031] Solvent: n-Heptane; Graphene sheet diameter 100nm, addition amount 0.7 parts; Main catalyst 0.08wt%, total co-catalyst concentration 0.2wt%, ratio 15:1; Polymerization 140℃, 1-Butene 3mol%; Finished product specifications: MFR=2.2g / 10min, density 0.940g / cm³, surface resistivity 7×10⁻⁶ 5 Ω, thermal conductivity 0.68W / (m・K), oxygen permeability 15cm³ / (m²・24h・atm).
[0032] Example 3: Solvent: Cyclohexane; Graphene sheet diameter 100 nm, addition amount 0.7 parts; Catalytic parameters same as in Example 2, polymerization 140℃, 1-butene 3 mol%; Finished product indicators: MFR=2.3 g / 10 min, density 0.941 g / cm³, surface resistivity 8×10 5 Ω, thermal conductivity 0.67W / (m・K), oxygen permeability 15cm³ / (m²・24h・atm).
[0033] Example 4:
[0034] Solvent: n-Heptane; Graphene sheet diameter 150nm, addition amount 1.2 parts; Main catalyst 0.12wt%, co-catalyst 0.3wt%, ratio 12:1; Polymerization 150℃, 1-Butene 4mol%; Finished product specifications: MFR=2.7g / 10min, density 0.939g / cm³, surface resistivity 4×10⁻⁶ 5 Ω, thermal conductivity 0.79W / (m・K), oxygen permeability 13cm³ / (m²・24h・atm).
[0035] Example 5:
[0036] Solvent: n-Heptane; Graphene sheet diameter 200nm, addition amount 2.0 parts; Main catalyst 0.15wt%, co-catalyst 0.4wt%, ratio 10:1; Polymerization 145℃, 1-Butene 4mol%; Finished product specifications: MFR=2.7g / 10min, density 0.940g / cm³, surface resistivity 8×10 4 Ω, thermal conductivity 0.88W / (m・K), oxygen permeability 11cm³ / (m²・24h・atm).
[0037] Example 6:
[0038] Solvent: xylene; graphene sheet diameter 200 nm, addition amount 2.0 parts; catalytic parameters same as in Example 5, polymerization 145℃, 1-butene 4 mol%; finished product indicators: MFR=2.8 g / 10 min, density 0.940 g / cm³, surface resistivity 6×10 4 Ω, thermal conductivity 0.89W / (m・K), oxygen permeability 11cm³ / (m²・24h・atm).
[0039] In summary, the data analysis shows that all parameters in the embodiments fall within the range defined in the claims. Compared to the blank comparative example, the thermal conductivity, antistatic properties, and oxygen barrier properties of the product prepared by this invention are significantly improved. As the amount of graphene added increases and the process parameters approach the optimal range, the modification effect is further optimized, fully demonstrating that the process of this invention is stable and reliable. The modified polyethylene particles prepared by the process of this invention possess high thermal conductivity, antistatic properties, and high oxygen barrier properties, and are mainly used in high-barrier food packaging films, geothermal transmission pipes, modified plastics for automotive interiors, and raw materials for heat dissipation shells of 5G equipment. They can also be extended to the processing of oil and gas corrosion-resistant pipes, lightweight aerospace components, antistatic precision instrument shells, and antibacterial preservation packaging.
[0040] Finally, it should be noted that the present invention is not limited to the above embodiments, and many variations are possible. All variations that can be directly derived or conceived by those skilled in the art from the disclosure of the present invention should be considered within the scope of protection of the present invention.
Claims
1. A method for preparing modified polyethylene by in-situ dispersion of graphene, characterized in that, The method, conducted entirely under nitrogen inert protection, includes the following preparation steps: (1) Preparation of graphene in situ dispersion: Graphene raw material is added to an inert organic solvent and homogenized at high speed for 1 to 3 hours under the conditions of 30 to 50°C and 7000 to 14000 rpm to obtain graphene in situ dispersion; the inert organic solvent is selected from any one of cyclohexane, n-heptane, and xylene; the graphene sheet diameter is 50 to 200 nm, the number of layers is ≤3, and the purity is >99.5%; the amount of graphene added is 0.3 to 2.0 parts by mass based on the mass of the inert organic solvent. (2) Catalytic polymerization reaction: The in-situ dispersion was transferred to a polymerization reactor, and the Ziegler-Natta composite catalyst was added. After the temperature was raised to the polymerization temperature, ethylene, the comonomer 1-butene, and a trace amount of hydrogen were introduced. Homogeneous polymerization was carried out at a constant temperature for 1 hour to obtain a polyethylene-graphene composite dispersion. The Ziegler-Natta catalyst was composed of titanium tetrachloride as the main catalyst, diethylaluminum chloride and MAO as the co-catalyst. The mass concentration of the main catalyst in the dispersion was 0.05-0.15 wt%, the total mass concentration of the co-catalyst was 0.1-0.4 wt%, and the mass ratio of diethylaluminum chloride to MAO was 10:1-20:
1. The polymerization temperature was 130-150℃. Based on the total molar amount of ethylene, the amount of 1-butene added was 2-4 mol%. (3) Flash evaporation and solvent removal: The polyethylene-graphene composite dispersion is flash-evaporated at a constant temperature to remove residual inert solvent and unreacted monomers, and graphene-modified polyethylene melt is obtained. (4) Extrusion granulation: The modified polyethylene melt is extruded and granulated by screw extrusion at a temperature of 210-230℃ to obtain graphene modified polyethylene granules.
2. The method for preparing modified polyethylene by in-situ dispersion of graphene according to claim 1, characterized in that: The preferred inert organic solvent is n-heptane.
3. A method for preparing modified polyethylene by in-situ dispersion of graphene according to claim 1, characterized in that: The graphene is preferably 100-200 nm in diameter, and the amount of graphene added is preferably 0.7-1.2 parts by mass of the inert organic solvent.
4. A method for preparing modified polyethylene by in-situ dispersion of graphene according to claim 1, 2, or 3, characterized in that: The preferred ratio of the co-catalyst diethylaluminum chloride to MAO is 12:1 to 15:
1.
5. A method for preparing modified polyethylene by in-situ dispersion of graphene according to claim 1, characterized in that: The preferred amount of 1-butene added is 3-4 mol of ethylene, and the preferred polymerization temperature is 140-150℃.
6. A method for preparing modified polyethylene by in-situ dispersion of graphene according to claim 1, characterized in that: Step (1) Homogenization conditions: preferred temperature 35-45℃, rotation speed 9000-12000rpm, homogenization time 1.5-2.5h.
7. A method for preparing modified polyethylene by in-situ dispersion of graphene according to claim 1, characterized in that: Step (4) Extrusion granulation is preferably performed at a processing temperature of 215-225℃.
8. The method for preparing modified polyethylene by in-situ dispersion of graphene according to claim 1, characterized in that: During the polymerization stage, trace amounts of hydrogen are used as molecular weight regulators to control the melt flow rate of the finished polyethylene product.
9. The graphene-modified polyethylene particulate material prepared according to the method of claim 1, 2, 3, 5, 6, 7, or 8, characterized in that: The product performance indicators meet the following requirements: melt flow rate > 2.0 g / 10 min under 2.16 kg weight conditions, density < 0.945 g / cm³, oxygen permeability < 20 cm³ / (m²・24h・atm), and surface resistivity < 10 Ω·cm. 7 Ω, thermal conductivity >0.51W / (m・K).
10. The graphene-modified polyethylene particulate material according to claim 9, characterized in that: Graphene-modified polyethylene granules can be used in high-barrier food packaging films, geothermal pipelines, modified plastics for automotive interiors, and raw materials for heat dissipation shells of 5G equipment.